Leverage dan Market Share sebagai Faktor Penentu Posisi Persaingan Pasar Perusahaan Manufaktur di Indonesia - Juwita Sari; Puput Tri Komalasari (Jurnal Bisnis dan Manajemen, 2021)
This study aims to examine the simultaneous relationship between leverage and market share as a determinant of market competition for manufacturing companies in Indonesia. The model used in this study is the TSLS (Two Stage Least Square) and testing with OLS (Ordinary Least Square), the testing tool used is SPSS. The object of research used in this study is a Manufacturing Company listed on the Indonesia Stock Exchange from 2015-2020 with a total of 122 companies that have fit with criteria for the research sample. The results of the study show that the two endogenous variables: leverage and market share, have a significant positive correlation with each other, which means that there is a simultaneous relationship between leverage policy and market share as an indicator of the competitive position of the product market.